2001
DOI: 10.1002/hipo.1048
|View full text |Cite
|
Sign up to set email alerts
|

Medial temporal and prefrontal contributions to working memory tasks with novel and familiar stimuli

Abstract: Lesions of parahippocampal structures impair performance of delayed matching tasks in nonhuman primates, suggesting a role for these structures in the maintenance of items in working memory and short-term stimulus matching. However, most human functional imaging studies have not shown medial temporal activation during working memory tasks and have primarily focused on functional magnetic resonance imaging (fMRI) signal intensity changes in the prefrontal and posterior parietal cortex. The goal of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
94
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(105 citation statements)
references
References 50 publications
10
94
1
Order By: Relevance
“…Our findings are consistent with recent neuroimaging findings that report activations of the hippocampus during visual WM tasks (Ranganath & D'Esposito, 2005). Some investigators interpreted these activations as establishment of an LTM trace for novel stimuli (Ranganath, Cohen, & Brozinsky, 2005;Ranganath & D'Esposito, 2005;Schon, Hasselmo, LoPresti, Tricarico, & Stern, 2004;Stern, Sherman, Kirchhoff, & Hasselmo, 2001), whereas others suggest that they reflected WM maintenance for certain classes of stimuli (Mitchell, Johnson, Raye, & D'Esposito, 2000). It is difficult to give a strong interpretation to these findings given that the majority of functional magnetic resonance imaging (fMRI) studies have not reported MTL activations during WM tasks (Postle, Stern, Rosen, & Corkin, 2000;Stern, Owen, et al, 2000;Cohen et al, 1997;Owen, Sahakian, Semple, Polkey, & Robbins, 1995).…”
Section: Interpreting Memory Deficits At Short Delayssupporting
confidence: 91%
“…Our findings are consistent with recent neuroimaging findings that report activations of the hippocampus during visual WM tasks (Ranganath & D'Esposito, 2005). Some investigators interpreted these activations as establishment of an LTM trace for novel stimuli (Ranganath, Cohen, & Brozinsky, 2005;Ranganath & D'Esposito, 2005;Schon, Hasselmo, LoPresti, Tricarico, & Stern, 2004;Stern, Sherman, Kirchhoff, & Hasselmo, 2001), whereas others suggest that they reflected WM maintenance for certain classes of stimuli (Mitchell, Johnson, Raye, & D'Esposito, 2000). It is difficult to give a strong interpretation to these findings given that the majority of functional magnetic resonance imaging (fMRI) studies have not reported MTL activations during WM tasks (Postle, Stern, Rosen, & Corkin, 2000;Stern, Owen, et al, 2000;Cohen et al, 1997;Owen, Sahakian, Semple, Polkey, & Robbins, 1995).…”
Section: Interpreting Memory Deficits At Short Delayssupporting
confidence: 91%
“…The process of selective attention is one in which an individual "selectively attends to some stimuli, or aspects of stimuli, in preference to others" ͑Kahneman, 1973͒, and is a vital component of one's ability to function in the environment. There are numerous studies emphasizing the role of the cortex in this ability to effectively suppress stimuli that are not relevant to the task at hand ͑e.g., Glosser and Goodglass, 1990;Knight et al, 1999;Rueckert and Grafman, 1996;Stern et al, 2001͒. Reviews of literature in cognitive functioning emphasize that individual differences in behavioral performance might best be explained by underlying differences in cortical inhibition ͑e.g., Dempster, 1992;Harnishfeger and Bjorkland, 1994͒.…”
Section: Discussionmentioning
confidence: 97%
“…Both HG and mPFC are implicated in working memory (Stern et al 2001), and recent animal studies have directly linked altered HG-mPFC functional connectivity in chronic pain to spatial working memory deficits (Cardoso-Cruz et al 2013). Additionally, HG-mPFC bidirectional interactions are necessary for making choices between different response strategies (Goto and Grace 2008), suggesting that HG-mPFC interactions are essential for mediating behaviorally relevant spiking patterns to utilize memory in driving goal-directed behavior (Goto and Grace 2008;Squire 1992).…”
Section: Discussionmentioning
confidence: 98%